Os desafios e a pertinência da escuta psicanalítica frente à toxicomania - Rutsatz, Patricia (2015)
The problem of abuse of legal and illegal substances has assumed alarming proportions worldwide. From a psychoanalytic perspective, the use of toxic substances can be understood as a possible means to relieve psychic pain. The contemporary setting has contributed important elements to the weakening of the subject's structuring processes, and the compulsion to use toxic substances. One sees the compulsive use of intoxication as a poor way to address the malaise. The overwhelming effect of substance abuse in the social field reveals the need to understand and overcome the challenges that this problem requires in clinical spaces that aim to intervene in that suffering. The theoretical section of this Thesis was titled "The role of drug abuse in the economy of psychic pain"and conceptualized the subject s junkie condition exploring the complex relationship with the psychic pain. From a literature review, we propose a reflection on the contributions that psychoanalysis has to relate to the demands of contemporary culture, the psychic subject, and the pain experience with the drug addiction phenomenon. The empirical section of this Dissertation called "The complexity and specificity of psychoanalytic listening in drug addiction", explored the complexity and specificity of the theoretical and technical factors involved in psychoanalysis of the drug addiction phenomenon. Therefore, we opted to use qualitative mathodological assumptions. Interviews were conducted with six psychoanalysts, three Brazilians and three Argentines, with experience of a minimum of five years of clinical practice in psychoanalysis. The material was analyzed through the Interpretative Analysis methodology and interpretation of the findings, using psychoanalysis. In order to present the system of work that guided this study, three assertions were formulated. The First Assertiveness was entitled "The challenge of sustaining the transfer analyst with psychoanalysis before a failure in the clinic," the Second Assertiveness was called "The construction of demand analysis and listening to the smuggling' transference" and "The potential harm reduction via listening to the other scene was the Third Assertiveness. The study allowed the affirmation of analytic listening as potential and singular subject access tools and the place which the toxins occupy in the subject s psychic economy, highlighting the relevance of the experience of speech and not the imposition of detoxification in building demand for treatment. Analysis of the material obtained from the professionals allowed us to reveal the impasses as well as the contributions of psychoanalysis to the field of drug addiction